2011
DOI: 10.3171/2010.9.spine09871
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically evoked, discrete-threshold electromyography in the extreme lateral interbody fusion approach

Abstract: Object Because the psoas muscle, which contains nerves of the lumbar plexus, is traversed during the extreme lateral interbody fusion (XLIF) approach, appropriate nerve monitoring is needed to avoid nerve injury during surgery and prevent approach-related neural deficit. This study was performed to assess the effectiveness of dynamically evoked electromyography (EMG) to detect and prevent neural injury during the XLIF approach. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
83
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(101 citation statements)
references
References 24 publications
5
83
1
3
Order By: Relevance
“…Tohmeh demonstrated that dynamically evoked, discrete-threshold electromyography reduces the risk of nerve injury during LLIF. However, even in this study, all cases with transient deficits had no concerning changes during intra-operative neuromonitoring assessment [12]. Furthermore, a case report by Houten shows two cases that had post-operative motor deficits following the transpsoas approach although the intra-operative monitoring did not detect anything [19].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Tohmeh demonstrated that dynamically evoked, discrete-threshold electromyography reduces the risk of nerve injury during LLIF. However, even in this study, all cases with transient deficits had no concerning changes during intra-operative neuromonitoring assessment [12]. Furthermore, a case report by Houten shows two cases that had post-operative motor deficits following the transpsoas approach although the intra-operative monitoring did not detect anything [19].…”
Section: Discussioncontrasting
confidence: 61%
“…Surgeons have theorized that this may be related to direct cutaneous nerve neuropraxia or an indirect mechanism via a psoas muscle inflammatory response due to mechanical dissection. The incidence of this varies considerably in the literature from 1 to 75% [2,[10][11][12]. Several studies have reported on post-operative neurologic deficits following LLIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from our systematic review that have characterized the complications of lateral transpsoas approaches (Table 2) included adverse medical outcomes (ileus, pneumonia, renal, pulmonary embolus, cardiac [26,27], anemia, volvulus [27], rhabdomyolysis [7], pleural effusion, sepsis [12]) and surgery-specific complications (vertebral fracture [14,26,27,32], end plate fracture [27], iatrogenic herniated nucleus pulposus [27], graft subsidence [7], sensory disturbance [14-16, 20, 26, 32, 33], Yes XLIF = extreme lumbar interbody fusion; ALIF = anterior lumbar interbody fusion; TDR = total disc replacement; fx = fracture; DDD = degenerative disc disease; HNP = herniated nucleus pulposus; EP = endplate; VB = vertebral body; OP = osteophyte; MI = myocardial infarction; DVT = deep venous thrombosis; PE = pulmonary embolism; A fib = atrial fibrillation; CSF = cerebrospinal fluid. motor deficits [12, 14-16, 20, 26, 27, 32, 33], incisional hernias [4,26], hardware failures [12,27], loss of fixation [15], malpositioned cage, retroperitoneal hemorrhage [32], hematoma [27],wound infection [12,20], durotomy, pneumothorax, and peritoneum perforation [33]). Second, none of the literature reviewed was of high quality.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,18,20,23,25 Therefore, neural monitoring is required for XLIF. 15,19,23 A dilator equipped with an electrode is inserted toward the vertebral region through the psoas major muscle while the threshold displayed on the monitor is observed. 19 Such surgery should be suspended when the insertion route is close to the lumbar plexus because of the invasive risk to the lumbar plexus.…”
mentioning
confidence: 99%